On the statistical convergence of (?, ?) type in paranormed spaces - Cinar, Muhammed; Karakas, Murat; Et, Mikail (Taylor & Francis Ltd, 2022)
The idea of (lambda, mu) statistical convergence was given by Mursaleen. The fundament aim of the article is to define and analyze the notion of (lambda, mu) -statistical convergence of double sequences and present some relations between the sets of S(lambda, mu) and S(theta, gamma); [V, lambda, mu] and [V, theta, gamma].
Keywords: Double sequences; Generalized statistical convergence; Paranormed space